Pokémon. Sun & Moon. 9 - Kusaka, Hidenori; Turnage, Bryant (VIZ Media, LLC, 2021)
Sun and Moon are trapped in Ultra Space with the Ultra Beasts and must find the pokémon Lunala and a way back to the Alolan Islands.